2005
DOI: 10.1111/j.1742-4801.2005.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

High glucose inhibits human epidermal keratinocyte proliferation for cellular studies on diabetes mellitus

Abstract: In order to more clarify the delayed wound healing in diabetes mellitus, we cultured the human epidermal keratinocytes in both 6 mM (control group) and 12 mM glucose (high-glucose group) of "complete" MCDB 153 medium. Hyperglycaemia slowed the rate of their proliferation and inhibited their DNA synthesis and the production of total proteins. By 1 month after primary seeding in high-glucose group, the cells ceased their proliferation, whereas the cells in control group grew for more than 40 days. Mean populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
4
41
0
1
Order By: Relevance
“…Pre-incubation of WT primary mouse KCs in 20 mM glucose for 72 h, traditionally used to simulate the hyperglycemic diabetic environment in vitro (Ingram et al , 2008; Suzuki et al , 2011), stopped migration in in vitro wounds (Figure 3a and b) and reduced cell proliferation (Figure 3c) (Lan et al , 2008; Spravchikov et al , 2001; Terashi et al , 2005). GM3S −/− cells migrated faster than WT cells by 24 h after wounding in normoglycemic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-incubation of WT primary mouse KCs in 20 mM glucose for 72 h, traditionally used to simulate the hyperglycemic diabetic environment in vitro (Ingram et al , 2008; Suzuki et al , 2011), stopped migration in in vitro wounds (Figure 3a and b) and reduced cell proliferation (Figure 3c) (Lan et al , 2008; Spravchikov et al , 2001; Terashi et al , 2005). GM3S −/− cells migrated faster than WT cells by 24 h after wounding in normoglycemic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…19 Prior studies revealed that chronic wound states in diabetes are related to the deficiency of functional stem cells, dysfunctional cellular response, and insufficient cell proliferation at the injury site, in which diabetic fibroblasts show selective impairments in discrete cellular processes critical for tissue repair including cellular migration, VEGF production, and the response to hypoxia. [23][24][25][26][27][28][29] In the genetically diabetic mice experimental model, the tail vein-injected fibrocytes was effective in improving wound closure. It was probably that the injected fibrocytes migrated into the wounds and recruited to compensate the dysfunctional resident dermal fibroblasts; in addition, it appeared to provide an additional, renewable source of functional progenitor cells to promote wound healing.…”
Section: Figurementioning
confidence: 99%
“…For example, both fibroblasts and endothelial progenitor cells from diabetic ulcers have been shown to exhibit impaired migration, proliferation, adhesion, and growth factor production. [4][5][6] This has led some to propose the application of fresh, unimpaired cells to nonhealing wounds as a means to reinitiate or replace the host tissue's wound-healing cascade. 7 Emerging work suggests that adipose-derived stromal cells (ASCs) may be useful for therapeutic wound-healing applications.…”
Section: Introductionmentioning
confidence: 99%